2017
DOI: 10.1128/iai.00898-16
|View full text |Cite
|
Sign up to set email alerts
|

MetQ of Neisseria gonorrhoeae Is a Surface-Expressed Antigen That Elicits Bactericidal and Functional Blocking Antibodies

Abstract: Neisseria gonorrhoeae, the causative agent of the sexually transmitted infection (STI) gonorrhea, is a growing public health threat for which a vaccine is urgently needed. We characterized the functional role of the gonococcal MetQ protein, which is the methionine binding component of an ABC transporter system, and assessed its potential as a candidate antigen for inclusion in a gonococcal vaccine. MetQ has been found to be highly conserved in all strains investigated to date, it is localized on the bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 78 publications
1
58
0
Order By: Relevance
“…The results of all software programs and the majority votes strategy revealed six additional CE proteins, four of which were found in the majority of examined strains (supplemental Table S6). In addition, literature searches for experimental evidence of protein surface exposure allowed assignment of BamE [NGO1780; (71)], SliC [NGO1063; (72)], MetQ [NGO2139; (30,73)], Ng-MIP [NGO1225; (30,74)], and BamG [NGO1985; (75)] to the cell surface. Subcellular location predictions for all proteins are listed in supplemental Table S8.…”
Section: Fig 2 Venn Diagrams Illustrating the Distribution Of Protementioning
confidence: 99%
“…The results of all software programs and the majority votes strategy revealed six additional CE proteins, four of which were found in the majority of examined strains (supplemental Table S6). In addition, literature searches for experimental evidence of protein surface exposure allowed assignment of BamE [NGO1780; (71)], SliC [NGO1063; (72)], MetQ [NGO2139; (30,73)], Ng-MIP [NGO1225; (30,74)], and BamG [NGO1985; (75)] to the cell surface. Subcellular location predictions for all proteins are listed in supplemental Table S8.…”
Section: Fig 2 Venn Diagrams Illustrating the Distribution Of Protementioning
confidence: 99%
“…The results of all software programs and the majority votes strategy revealed six additional CE proteins, four of which were found in the majority of examined strains (Supplemental Table S6). In addition, literature searches for experimental evidence of protein surface exposure allowed assignment of BamE [NGO1780; (72)], SliC [NGO1063; (73)], MetQ [NGO2139; (30, 74)], Ng-MIP [NGO1225; (30, 75)], and BamG [NGO1985; (76)] to the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Ng-MIP-like proteins exist in C. trachomatis , G. vaginalis , and P. ruminicola ; BamA and NGO1559 homologs were found in C. trachomatis and P. ruminicola . MetQ, a methionine transporter (74), was the only proteomics-derived vaccine candidate with homologs across all examined bacteria with the exception of C. trachomatis and P. ruminicola . Further, we detected protein homologs of PilQ in two C. trachomatis strains and MtrE and ZnuD in P. ruminicola ; these three proteins were absent in commensal species.…”
Section: Resultsmentioning
confidence: 99%
“…APJL_0922 encodes a protein with homology to d-methionine-binding lipoprotein MetQ of other bacteria. Previous studies have suggested that MetQ is involved in methionine transport, cell adherence, intracellular survival in Neisseria gonorrhoeae, and more importantly, the surface-located MetQ protein is a promising vaccine candidate that elicits bactericidal and functional blocking antibodies 38 . The A. pleuropneumoniae TolA protein is homologous to the colicin transporter of Neisseria sicca, and contains 15 copies of EAEAKAKA in the intragenic tandem repeat (TR) region at the N terminus, and is implicated in E. coli colicin uptake, filamentous phage infection, and detergent tolerance 39 .…”
Section: Discussionmentioning
confidence: 99%